2008
DOI: 10.1080/13625180802011302
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to condom use

Abstract: Their cost evidently poses a barrier to the use of condoms by the poor. Beside social stigmas and personal reluctance, prevailing moral norms and religious interdicts also adversely affect use of these devices in many communities. Because of their disastrous consequences in the domain of public health each of these barriers must be effectively addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 49 publications
14
94
2
5
Order By: Relevance
“…Previous studies revealed that the barriers to cervical cancer preventive behaviors were significantly related to the intent to practice these behaviors (Kim, 2009;Waller, Bartoszek, Marlow, & Wardle, 2009). Several barriers to condom use have been reported, such as embarrassment, cost, moral values, ethnic and religious factors, gender inequality, and the lack of a dialogue between partners (Moore et al, 2008;Sarkar, 2008). Barriers to Pap tests include anxiety, embarrassment, and pain (Al-Naggar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the barriers to cervical cancer preventive behaviors were significantly related to the intent to practice these behaviors (Kim, 2009;Waller, Bartoszek, Marlow, & Wardle, 2009). Several barriers to condom use have been reported, such as embarrassment, cost, moral values, ethnic and religious factors, gender inequality, and the lack of a dialogue between partners (Moore et al, 2008;Sarkar, 2008). Barriers to Pap tests include anxiety, embarrassment, and pain (Al-Naggar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The affordability of contraception may limit access for some low affluence groups 20 , and the influence of perceived peer norms and the quality of parent-adolescent discussions regarding condom use may also contribute to socioeconomic inequalities 21 . Access to consistent and universal sexual health education 22,23 and age-appropriate sexual health services 13,24 should be maintained, but the strong link between socioeconomic disadvantage and risky sexual health behaviours suggests that additional targeted interventions should also be considered e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Male partners may resist use of condoms in marital and steady relationships because sex ought to be natural. This attitude has previously been described in studies conducted both in young and older women [29] and underlines the difficulty for women with HIV to negotiate safer sex practices. Therefore, trust and negotiation for condom use should be addressed in educational programs during counseling.…”
Section: Mistrust and Lack Of Negotiationmentioning
confidence: 99%